Investigation of Natural Circulation Flow Under Steady-State Conditions Using a Rectangular Loop - Roswandi, Iwan; Dimas; Gunawan, Hyundianto Arif; Budiman, Arif Adtyas; Amelia, Almira Citra; Sanda; Tjahjono, Hendro; Juarsa, Mulya (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
Passive safety systems, particularly during active system failures, have become a significant concern. Understanding natural circulation phenomena is crucial for developing passive cooling systems in nuclear power plants. With its significant findings, this study examines the flow patterns under steady-state conditions and assesses the Grashof number. The experimental approach involved maintaining temperature differences of 60 °C, 70 °C, 80 °C, and 90 °C for 3 hours, with three replications. The temperature alterations impact water’s physical properties, such as density, viscosity, and specific heat. The calculations reveal that the minimum Grashof number that occurs at 60 °C is 2.49×10¹², while the maximum observed at 90 °C is 9.42×10¹², with an R² value of 0.96533. The observation of turbulent flow patterns during each temperature fluctuation, which aligns with previous research on the Ress value of Grm/NG, has significant implications for the design and operation of passive safety systems in nuclear power plants.